2011
DOI: 10.1080/02786826.2010.517580
|View full text |Cite
|
Sign up to set email alerts
|

Oligomer Content of α-Pinene Secondary Organic Aerosol

Abstract: The quantity, extraction efficiency, and molecular composition of non-volatile oligomeric species in SOA generated by the reaction of α-pinene with ozone were studied. Two different methods of determining the total particulate mass in the reaction chamber were compared and found to be in good agreement when changes in the partitioning of semi-volatile compounds to the particle phase during measurement were properly handled. Almost all of the nonvolatile organic carbon formed by the reaction was collected and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 24 publications
5
125
1
1
Order By: Relevance
“…4b. The total oligomer signal intensity was comparable to our previous study of α-pinene SOA formed under similar reaction conditions, where the oligomer content was experimentally determined to be about 50 % of the total SOA mass (Hall IV and Johnston, 2011). For the Tu study, we estimate the NVOC mixing ratio to be approximately 2 ppbv based on the yield estimate of Ehn et al (2014) for β-pinene ozonolysis.…”
Section: Comparison To Recent Experimental Measurements and Atmosphersupporting
confidence: 57%
See 1 more Smart Citation
“…4b. The total oligomer signal intensity was comparable to our previous study of α-pinene SOA formed under similar reaction conditions, where the oligomer content was experimentally determined to be about 50 % of the total SOA mass (Hall IV and Johnston, 2011). For the Tu study, we estimate the NVOC mixing ratio to be approximately 2 ppbv based on the yield estimate of Ehn et al (2014) for β-pinene ozonolysis.…”
Section: Comparison To Recent Experimental Measurements and Atmosphersupporting
confidence: 57%
“…Reactions such as these increase the aerosol yield by forming additional SOA beyond what would be expected from partitioning alone, if they form non-volatile products from semi-volatile reactants in the particle phase (Lopez-Hilfiker et al, 2016;Shiraiwa et al, 2014). Experimental measurements have shown that oligomers can constitute up to about 50 % of the mass of SOA produced from biogenic precursors in laboratory reactors, though it is not clear how much of the oligomeric matter is produced from semi-volatile vs. non-volatile precursors (Hall IV and Johnston, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…According to several studies SOA particles may contain oligomers, polymers and other high molecular weight molecules (Tolocka et al, 2004;Gao et al, 2004;Kalberer et al, 2004;Hallquist et al, 2009;Hall IV and Johnston, 2011;Kundu et al, 2012). Such oligomers and polymers are likely to affect the phase state of SOA particles.…”
Section: Discussionmentioning
confidence: 99%
“…SVOC can react further to produce nonvolatile organic compounds (NVOC) that reside fully in the particle phase [3,4]. Recent measurements of laboratory generated SOA show that oligomers formed by the reaction of SVOC monomers to produce mostly dimer and trimer species constitute more than half of the NVOC [5,6]. Because of the large number of monomer building blocks and reactions that may couple them together, these oligomers exhibit great molecular complexity.…”
Section: Introductionmentioning
confidence: 99%